Learning Head and Neck Anatomy Through a Radiological Imaging Platform - Daniel Hussey; Abigail V. Shaw; Pamela L. Brian; Michelle D. Lazarus (Association of American Medical Colleges, 2022)
Introduction Head and neck anatomy is complex for students to learn and educators to teach. Instructing students on anatomy using radiological imaging can aid comprehension and prepare them for future clinical practice. Computer-aided anatomy instruction is accessible to diverse learners and avoids barriers identified with face-to-face teaching. Methods We designed a self-guided PowerPoint tutorial with multiple medical imaging modalities, clinical correlations, and self-review questions incorporated throughout. The tutorial was evaluated with a group of 178 Australian preclinical medical students who had prior teaching related to head and neck anatomy. Student participants were divided into experimental and control groups. Participants completed two knowledge assessments: experimental group before and after tutorial engagement and control group before tutorial engagement. All participants were invited to provide feedback on their experiences with the tutorial via questionnaires. Results Engagement with the tutorial improved overall head and neck anatomy knowledge (p < .001). Knowledge outcomes were maintained across question group type (e.g., multiple-choice questions, identification, and short-answer questions; p < .05), with participants reporting 96% overall positive feedback related to the tutorial experience. Discussion Given the improved outcomes following tutorial exposure, our results suggest that this tutorial is efficacious when used in concert with existing anatomy curricula. Participants' perceived value of the tutorial additionally suggests that it would be taken up well by medical students and is an effective addition to the existing tutorial series. Further research is needed to assess the tutorial's use as a stand-alone addition to the anatomy curriculum.